The 2024 Ranking List of Hungarian Scientists in the Field of Scientometrics - Gyula Mester (Analecta)
The article presents the 2024 ranking of Hungarian researchers in the field of Scientometrics. The ranking is presented primarily according to the h-index of researchers. Researchers with matching h-index are ranked by the number of citations. The ranking list includes 12 researchers. The h-index can be determined from Web of Science, Scopus, Google Scholar, the Hungarian Scientific Works Repository and the programs Tud-O-Méter, Publish or Perish. The ranking is edited using the Google Scholar web database.